SEASONALITY EFFECTS IN KAZAKHSTAN STOCK EXCHANGE (KASE) INDEX - Mutkarim, Assem; Orumbayeva, Sara; Nursalim, Madina (Nazarbayev University, Graduate School of Business, 2021)
We investigate whether there exist seasonal anomalies in the Kaza- khstan Stock Exchange (KASE) index. We focus on two well-known ef- fects in capital markets: day-of-the-week and month-of-the-year e ects af- ter controlling macroeconomic variables, crisis periods, and world market movement. Moreover, we construct the KASE Total Return index to con- sider dividends as a potential cause of seasonality in the index returns. The empirical evidence indicates that there are negative Monday and pos- itive Friday e ects in KASE index. However, the negative Monday e ect might result from a decrease in prices on ex-dividend dates. The positive Friday e ect can be explained by investors' sentiments before the holidays. We nd no month-of-the-year e ect in the KASE index. Since there is no prior research on seasonality in the local market, our study reveals notable results and initiates a discussion on this topic.
Keywords: KAS; SEASONALITY EFFECTS; Type of access: Restricted